Peroral cholangioscopy: past, present and future - Yuki Tanisaka; Robert Hawes (Clinical Endoscopy)
Endoscopic retrograde cholangiopancreatography (ERCP) is the gold standard for the evaluation of biliary strictures and the management of bile duct stones. However, standard ERCP techniques sometimes fail for both indications. In such situations, peroral cholangioscopy (POCS), which allows direct visualization of the bile duct, can play a significant role in diagnosis and treatment. Direct visualization using POCS can help differentiate between malignant and benign conditions and is more accurate in defining the extent of cholangiocarcinoma. Furthermore, POCS enables visually guided biopsies. Certain types of difficult bile duct stones, such as impacted and intrahepatic stones, require POCS for visually guided lithotripsy. Recent advancements in POCS will broaden its applicability and improve its diagnostic utility. In this review, we provide perspectives on the past, present, and future of POCS.